Low-Frequency Oscillation Mitigation usin an Optimal Coordination of CES and PSS based on BA - Dwi Lastomo; Herlambang Setiadi; Galih Bangga; Imam Wahyudi Farid; Muhammad Faisal; Peter Go Hutomo; Taurista Perdana Syawitri; Louis Putra; Yongki Hendranata; Kristiadi Stefanus; Chairunnisa Chairunnisa; Andri Ashfahani; Ahmad Sabila (IAES Indonesia Section, 2018)
Small signal stability represents the reliability of generator for transferring electrical energy to the consumers. The stress of the generator increases proportionally with the increasing number of load demand as well as the uncertainty characteristic of the load demand. This condition makes the small signal stability performance of power system become vulnerable. This problem can be handled using power system stabilizer (PSS) which is installed in the excitation system. However, PSS alone is not enough to deal with the uncertainty of load issue because PSS supplies only an additional signal without providing extra active power to the grid. Hence, utilizing capacitor energy storage (CES) may solve the load demand and uncertainty issues. This paper proposes a coordination between CES and PSS to mitigate oscillatory behavior of the power system. Moreover, bat algorithm is used as an optimization method for designing the coordinated controller between CES and PSS. In order to assess the proposed method, a multi-machine two-area power system is applied as the test system. Eigenvalue, damping ratio, and time domain simulations are performed to examine the significant results of the proposed method. From the simulation, it is found that the present proposal is able to mitigate the oscillatory behavior of the power system by increasing damping performance from 4.9% to 59.9%.